Emotional intelligence, coping, and teachers' beliefs: keys to preventing school dropout - Ferrara, Gabriella; Pedone, Francesca; Moscato, Maria (Form@re - Open Journal per la formazione in rete, 2025)
This study addresses the issue of school dropout, recognized in the scientific literature as one of the main challenges within the educational system, with significant social and economic implications. In addition to socio-economic factors, teaching quality, and student motivation, the research explores a less examined aspect: the influence of teachers’ implicit beliefs on instructional practices and relationships with students. The study investigates the role of emotional intelligence, coping strategies, and the quality of the teacher-student relationship, using three standardized instruments (TEIQue, COPE-NVI, and STRS) on a sample of 1,141 teachers from different school levels. The collected data were statistically analyzed to assess the associations among the variables. The results confirm the initial hypotheses, highlighting that fostering emotional awareness and effective coping strategies among teachers can improve the school climate and help prevent school dropout. Intelligenza emotiva, coping e credenze degli insegnanti: chiavi per prevenire la dispersione scolastica. Il presente studio affronta il tema dell’abbandono scolastico, riconosciuto dalla letteratura scientifica come una delle principali sfide del sistema educativo, con rilevanti implicazioni sociali ed economiche. Oltre ai fattori socio-economici, alla qualità dell’insegnamento e alla motivazione degli studenti, viene analizzato un aspetto meno esplorato: l’influenza delle credenze implicite degli insegnanti sulle pratiche didattiche e sulle relazioni con gli studenti. La ricerca indaga il ruolo dell’intelligenza emotiva, delle strategie di coping e della qualità della relazione insegnante-studente, attraverso tre strumenti standardizzati (TEIQue, COPE-NVI e STRS), su un campione di 1.141 docenti di diversi ordini scolastici. I dati raccolti sono stati analizzati statisticamente per valutare le associazioni tra le variabili. I risultati confermano le ipotesi iniziali, evidenziando come promuovere la consapevolezza emotiva e strategie di coping efficaci tra gli insegnanti possa migliorare il clima scolastico e contribuire a prevenire l’abbandono scolastico.